Perlindungan Musytari Terhadap Klausula Baku Dalam Pembiayaan Murabahah Bil Wakalah PT. Bank BRI Syariah, Tbk. - Valeria Zahara Zulkarnaen (Lex Renaissance, 2020)
This research examines the existence of a clause in the Murabahah bil Wakalah contract at a bank which states that if based on the bank's assessment the collateral is no longer sufficient to guarantee debt payment, Musytari is obliged to add other items as collateral. Therefore, two problems arise: first about the legality of the clause; and second, the role of the notary in enforcing the implementation of the taswiyah principle in the Murabahah bil Wakalah contract. This type of research is normative and empirical, with literature and document studies, along with interviewing sources, and analyzed through a statutory approach, with qualitative methods. The results of the study conclude, first, the clause of adding collateral by the bank to Musytari is not in accordance with one of the pillars of the contract, namely Taswiyah, but is still legal as it is made in the presence of a notary; second, the role of a notary in the Murabahah bil Wakalah contract is to provide legal counseling to Musytari if the bank requires additional collateral to be fulfilled.